If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z+2-3z=8+2z-4
We move all terms to the left:
6z+2-3z-(8+2z-4)=0
We add all the numbers together, and all the variables
6z-3z-(2z+4)+2=0
We add all the numbers together, and all the variables
3z-(2z+4)+2=0
We get rid of parentheses
3z-2z-4+2=0
We add all the numbers together, and all the variables
z-2=0
We move all terms containing z to the left, all other terms to the right
z=2
| 3-7x+19=-4x-5-2x | | 6c-11=-2c+5-15 | | g-4g=23 | | a=a-37+a-32 | | (x+15)+x=4x-20 | | 4/5m=10 | | 12-4w=6w-11 | | 3(4+2x)–8=34 | | -15+6r=-7r+8r | | 8m=4m+24 | | -27-9,5x=-14x-9 | | 24x(x+2=0 | | 0.5x+1.25=2.75-0.5x | | 10(-6+r)=120 | | 15-2=7-5x | | (2.5+y)^2=1 | | v=v-48+v-50 | | 4yy=2.4 | | h3−1=3 | | 6=-14+8x+-6x-15 | | (½)x+7=-3 | | 60x+40=0 | | 9(8d)-58=12d-2 | | -6/15=2x/35 | | 49n=0 | | Y=16x+48 | | 1+6.9x=-1.8+5.9x | | 2r=7.92 | | R-5=11+4-2r+4 | | 3+x/3=-5 | | 10-4c=-3c | | a-(-3)=-12 |